The Influence of Product Quality, Brand Image, and Content Marketing on Consumer Satisfaction (Study on Roti Mox in Surabaya) - Amelia Dwi Lestari; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the significant effect of Product Quality, Brand Image, and Content Marketing both simultaneously and partially on Consumer Satisfaction on Roti Mox products in Surabaya. This type of research is associative research with a quantitative approach. Variable measurement uses a Likert scale with criteria ranging from strongly disagree to strongly agree. This sampling technique uses a non-probability sampling method by applying a purposive sampling approach. The population used in this study were active followers of Instagram @rotimox in Surabaya City with a sample size of 100 respondents. The data collection method used a questionnaire distributed to respondents who met the criteria. The data analysis technique used the SPSS version 30 program. This study states that the variables Product Quality, Brand Image, and Content Marketing simultaneously have a significant effect on Consumer Satisfaction of Roti Mox products in Surabaya. The results of the study also showed that there was a positive and significant effect of Product Quality, Brand Image, and Content Marketing partially on Consumer Satisfaction of Roti Mox products in Surabaya.